Huntington disease and Huntington disease‐like in a case series from Brazil. (17th October 2013) - Castilhos, R.M.; Souza, A.F.D.; Furtado, G.V.; Gheno, T.C.; Silva, A.L.; Vargas, F.R.; Lima, M.‐A.F.D.; Barsottini, O.; Pedroso, J.L.; Godeiro, C.; Salarini, D.; Pereira, E.T.; et al.
<x xml:space="preserve">Abstract</x> The aim of this study was to identify the relative frequency of Huntington's disease (HD) and HD‐like (HDL) disorders HDL1, HDL2, spinocerebellar ataxia type 2 (SCA2), SCA17, dentatorubral‐pallidoluysian degeneration (DRPLA), benign hereditary chorea, neuroferritinopathy and chorea‐acanthocytosis (CHAC), in a series of Brazilian families. Patients were recruited in seven centers if they or their relatives presented at least chorea, besides other findings. Molecular studies of HTT, ATXN2, TBP, ATN1, JPH3, FTL, NKX2‐1/TITF1 and VPS13A genes were performed. A total of 104 families were ascertained from 2001 to 2012: 71 families from South, 25 from Southeast and 8 from Northeast Brazil. There were 93 HD, 4 HDL2 and 1 SCA2 families. Eleven of 104 index cases did not have a family history: 10 with HD. Clinical characteristics were similar between HD and non‐HD cases. In HD, the median expanded (CAG)n (range) was 44 (40–81) units; R2 between expanded HTT and age‐at‐onset (AO) was 0.55 (p = 0.0001, Pearson). HDL2 was found in Rio de Janeiro (2 of 9 families) and Rio Grande do Sul states (2 of 68 families). We detected HD in 89.4%, HDL2 in 3.8% and SCA2 in 1% of 104 Brazilian families. There were no cases of HDL1, SCA17, DRPLA, neuroferritinopathy, benign hereditary chorea or CHAC. Only six families (5.8%) remained without diagnosis.